Revision of Thai Dissomphalus Ashmead, 1893 (Hymenoptera, Bethylidae), with description of twenty four new species - Mugrabi, Daniele F.; Azevedo, Celso O. (Zootaxa, 2013)
The Thai Dissomphalus classification is reviewed, and 29 species are recognized. Previously described species, D. browni Terayama, D. chiangmaiensis Terayama, and D. thaianus Terayama had their known distribution and taxonomic variations broadened. Dissomphalus wusheanus Terayama is newly recorded from Thailand. Twenty-four new species, D. epitus Mugrabi & Azevedo, sp. nov., D. verus Mugrabi & Azevedo, sp. nov., D. prilus Mugrabi & Azevedo, sp. nov.,D. daneus Mugrabi & Azevedo, sp. nov., D. gabrus Mugrabi & Azevedo, sp. nov., D. gionus Mugrabi & Azevedo, sp. nov., D. cherrus Mugrabi & Azevedo, sp. nov., D. julius Mugrabi & Azevedo, sp. nov., D. davus Mugrabi & Azevedo, sp. nov., D. zethus Mugrabi & Azevedo, sp. nov., D. hetus Mugrabi & Azevedo, sp. nov., D. joelus Mugrabi & Azevedo, sp. nov., D. nandus Mugrabi & Azevedo, sp. nov., D. jubus Mugrabi & Azevedo, sp. nov., D. kelsus Mugrabi & Azevedo, sp. nov., D. turinus Mugrabi & Azevedo, sp. nov., D. paulus Mugrabi & Azevedo, sp. nov., D. barbus Mugrabi & Azevedo, sp. nov., D. robus Mugrabi & Azevedo, sp. nov., D. geanus Mugrabi & Azevedo, sp. nov., D. magnetus Mugrabi & Azevedo, sp. nov., D. lidinus Mugrabi & Azevedo, sp. nov., D. mugrus Mugrabi & Azevedo, sp. nov. and D. ferrerus Mugrabi & Azevedo, sp. nov., are described and illustrated. A key to the males of Dissomphalus from the Oriental region is provided.